The role of innate immune responses against two strains of PEDV (S INDEL and non-S INDEL) in newborn and weaned piglets inoculated by combined orogastric and intranasal routes - López-Figueroa, C.; Cano, E.; Navarro, N.; Pérez, M.; López, R.; Skovgaard, K.; Vorsholt, H.; Heegaard, P. M. H.; Vergara-Alert, J.; Segalés, J. (Frontiers in Immunology, 2025)
IntroductionPorcine epidemic diarrhea (PED) is a severe gastrointestinal disease in swine caused by PED virus (PEDV), leading to significant economic losses worldwide. Newborn piglets are especially vulnerable, with nearly 100% mortality, unlike older pigs. Disease severity also varies depending on the PEDV strain, with non-S INDEL strains being more virulent than S INDEL ones.MethodsThis study examined early pathogenesis and innate immunity in 5-day-old suckling and 5-week-old weaned piglets (n=8 per age group, 4 per strain) inoculated with S INDEL or non-S INDEL PEDV strains via combined orogastric and intranasal route. Age matched negative controls (n=3 per age group) were included. Body weight, temperature, and clinical signs were monitored for 48 hours post-inoculation (hpi). PEDV RNA levels were assessed in rectal swabs (RS) at 0 and 48 hpi, while pathological analyses and viral RNA loads were measured in jejunal content and intestinal mucosa. Gene expression of 75 selected antiviral and inflammatory genes were determined in laser capture microdissection (LCM)–derived jejunal samples using microfluidic qPCR at 48 hpi.ResultsSuckling piglets showed severe clinical signs, while weaned piglets were mostly asymptomatic at 48 hpi. In general, clinical signs and lesions in suckling piglets were similar, regardless of the PEDV strain. Both viral strains produced comparable viral RNA loads in the small intestine and feces, as well as consistent villous atrophy and fusion across age groups. In LCM-derived jejunal samples, weaned piglets had higher expression of antiviral genes (type I/III interferons, ISGs) and Th1/Th17 pro-inflammatory genes, particularly with the non-S INDEL strain. Conversely, the anti-inflammatory cytokine IL-10 was overexpressed in suckling compared to weaned piglets for both strains.DiscussionOverall, PEDV-induced intestinal damage, viral replication, and excretion were similar in studied groups regardless of viral strain or piglet age. The reduced clinical severity in weaned piglets may result from their stronger intestinal antiviral and pro-inflammatory response.